Is there an S&P 500 Index effect? - Maria Kasch; Asani Sarkar (Federal Reserve Bank of New York, 2011)
We find that the firms included in the S&P 500 index are characterized by large increases in earnings, appreciation in market value, and positive price momentum in the period preceding their index inclusion. This strong preinclusion performance predicts 1) the permanent increase in market value and 2) the change in return comovement, reflected in declines of size, value, and momentum betas, following index inclusion. Nonevent control firms with similar performance experience similar appreciation in value and changes in comovement coincident with the event firms. Our results indicate that - after accounting for the firms' extraordinary preinclusion performance - index inclusion has no permanent effect on value and comovement.
Keywords: G10; G12; G14; 330; S&P 500 inclusions; preinclusion performance; earnings; factor betas; value effect